Pengembangan Teknik Pemasaran Dan Inovasi Untuk Meningkatkan Kualitas Pelayanan Kedai Vespa Palu - Arin Aurizal Ishak; Faruq A.H Lamusa; Harnida Wahyuni Adda (Pusat Riset dan Inovasi Nasional, 2023)
Kedai Vespa Palu is a coffee shop business that has been established since 2017 which is engaged in the culinary field. With the main sale of coffee-type drinks. Kedai Vespa Palu in running its business certainly requires financial management of operational management and strategies to fulfill the sustainability of the business. By doing operational management and strategic management and doing business analysis to maintain the sustainability of the business. as for the business results that have been achieved by the hammer vespa shop, namely raw material management, operational management and strategies that are useful for increasing services and turnover of hammer vespa shops. Kedai Vespa Palu will continue to strive to improve the quality of servants and operations, and strategies to achieve even greater targets to develop the business.